2001
DOI: 10.1128/iai.69.11.6823-6830.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis Autoregulates Pertussis Toxin Production through the Metabolism of Cysteine

Abstract: 2؊ . Therefore, the combined presence and metabolism of cysteine may be an important mechanism in the pathogenesis of B. pertussis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
0
30
0
3
Order By: Relevance
“…In Mycobacterium tuberculosis, the cysDNC operon involved in the sulfate activation pathway forms a stress-induced operon (60), while many thiol and cysteine metabolism genes are part of the sigH regulon necessary for optimal survival of the bacterium in macrophages (52). Cysteine metabolism is also involved in the regulation of toxin in Bordetella pertussis (4), and autoinducer 2, a signaling molecule derivative of the sulfur metabolism conserved in both gram-positive and gram-negative bacteria, is involved in interspecies communication and regulation of virulence factors (54,68). Lastly, methionine is one of the key amino acids limiting the growth of Lactococcus lactis in dairy fermentations.…”
mentioning
confidence: 99%
“…In Mycobacterium tuberculosis, the cysDNC operon involved in the sulfate activation pathway forms a stress-induced operon (60), while many thiol and cysteine metabolism genes are part of the sigH regulon necessary for optimal survival of the bacterium in macrophages (52). Cysteine metabolism is also involved in the regulation of toxin in Bordetella pertussis (4), and autoinducer 2, a signaling molecule derivative of the sulfur metabolism conserved in both gram-positive and gram-negative bacteria, is involved in interspecies communication and regulation of virulence factors (54,68). Lastly, methionine is one of the key amino acids limiting the growth of Lactococcus lactis in dairy fermentations.…”
mentioning
confidence: 99%
“…Porém, com concentrações de 300 mM, a pureza radioquímica foi inferior aos 90%. Em teoria, este estudo indicou que o complexo radiomarcado não apresentaria transquelação in vivo, uma vez que a concentração de cisteína no organismo é muito baixa, sendo que no plasma humano ela varia entre 0,03 e 0,108 mM (Bogdan et al, 2001;Medical, 2006). Quando a análise dos dados é feita em relação ao tempo de incubação de 4 h, pôde-se constatar um pequeno decréscimo na estabilidade se comparado com os resultados de uma hora.…”
Section: Discussionunclassified
“…Sulfate has been shown to modulate, or down-regulate, transcription of the Bvg-regulated genes, including pertussis toxin (19) and, recently, bacterial conversion of cysteine to sulfate has been reported to promote modulation (2). Assembled pertussis toxin accumulates in the periplasm prior to secretion.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Under nonpermissive conditions, such as in the presence of high levels of sulfate ions, transcription of the B. pertussis virulence factors, including pertussis toxin, is repressed (19). Recently, it has been demonstrated that cysteine in the culture medium can serve as a precursor for sulfate production, which then modulates expression of the Bvg-regulated genes (2). Cysteine has been reported to be an essential amino acid for growth of B. pertussis, an observation that is supported by the presence of defective copies of the genes for cysteine biosynthesis in the preliminary genome sequence of B. pertussis that are intact in the preliminary genome of Bordetella bronchiseptica.…”
mentioning
confidence: 99%